GENERAL PREVALENCE OF HELICOBACTER PYLORI INFECTION IN DYSPEPTIC POPULATION OF ISLAMABAD, PAKISTAN - Qureshi, T. Z.; Saleem, K.; Bilal, R.; Zafar, S. (The Nucleus, 2020)
Helicobacter pylori was known as campylobacter pyloridis in the beginning of the twentieth century. Doenges was the first to find this bacterium in the autopsy specimens of stomach using haematoxylin and eosin stains. In 1940 Freedburg and Baron carried out a study on 35 partial gastrectomy specimens and found spirochetes in 37% after a long search. A major breakthrough occurred with the advent of fibroptic biopsy technique permitting the biopsy of stomach. Then in 1975 Steer and Colin Jones observed gram negative bacilli in 80% of patients with gastric ulcer. The bacterium was closely associated with the surface epithelium, both within and between pits. These microorganisms were poorly stained by haematoxylin and eosin stains but could be seen easily with Warthin Starry silver stain. Later on, a heavy growth of campylobacter like organism was found on non-selective culture media and so the first culture of helicobacter pylori was achieved in April 1982. Since then eight other helicobacter species have been found, one in man and the remainder in other animals including birds. The organism may remain silent for years or produce serious gastric disorders in the beginning. Many studies have been conducted on asymptomatic healthy individuals but its presence in dyspeptic patients has always been ignored and dyspepsia has been treated as a result of over acid production This study was conducted to determine the prevalence of helicobacter pylori [hp] infection in dyspeptic population of Islamabad using 13C urea breath test, and to find the possible role of water in bug transmission. We have also tried to assess the type of gastric pathology resulted by bacterial colonization in stomach. A total of 278 individuals were studied. Out of these 115 who had serious complaints/symptoms were sent for endoscopy to get the antral biopsy sample. Breath samples of dyspeptic individuals were sent to Isotope Application Division, PINSTECH for 13C/12C isotope ratio analysis using Mass Spectrometer. Water drinking habits of patients were recorded to assess the possible role of drinking water in bacterial transmission to human stomachs. Analysis of data obtained by mass spectrometry showed an overall prevalence of 66.5%. Majority of our subjects used unboiled water. Therefore, use of unboiled drinking water could be the most possible cause of this infection. Chronic antral gastritis was the predominant endoscopic pathology seen in infective patients. We, therefore, conclude that prevalence of H.pylori infection is high in Islamabad region mainly due to the use of contaminated drinking water.